Vector Biology: Tyrosine Degradation Protects Blood Feeders from Death via La Grande Bouffe - Kopáček, Petr; Perner, Jan (Current biology, 2016)
Blood-feeding arthropods digest vast amounts of host-blood nutrients. A new study suggests that tyrosine degradation is essential for the survival of blood-fed kissing bugs, mosquitoes, and ticks. This finding presents a promising target for the control of these disease vectors.
Keywords: Disease Vectors; Feeding Behavior; Tyrosine; smrt; infekce přenášené vektorem; tyrosin; lidé; Animals; Death; Insect Vectors; stravovací zvyklosti; Humans; zvířata; Culicidae; Arthropods; členovci; hmyz - vektory